Composition Analysis of Writing Materials in Cairo Genizah Documents Cambridge Genizah Studies Series, Volume 15 - Cohen, Zina (Études sur le judaïsme médiéval, 2021)
This work investigates the different writing materials in use in Egypt during the 11th century and the reason for their diversity.; Readership: Academics and specialists working in the Cairo Genizah and in writing material characterization.